Use of applications for leaching Learning Chemistry (Research, Society and Development, 2020)
Technology and education have always had a loving relationship, especially in the classroom. For Education in Chemistry, smartphones and their Apps can provide experiences that were previously restricted to a laboratory experiment. The purpose of this study was to investigate through an evaluation the use of the Periodic Table Quiz applications and the Educalabs Periodic Table in the classroom, how these technologies can be integrated into teaching and what are their effects on student learning. It was held at the Municipal School of Primary Education II Roberto Antunes de Freitas in the city of Quiterianópolis-CE, in 02 classes of the 9th grade, comprising 32 students, with a methodology based on a descriptive study, empirical basis and qualitative nature. The results showed the contribution and potential that the applications offer in the learning of chemical concepts. After using these, it can be noticed that there were more correct answers in 08 of the 10 questions proposed, and 100% of the students stated that their interest in the subject increased, so they could verify the validity of exploring chemistry contents through these applications since they offer more interactive content that engages the student's genuine interest in participating in the process.